Behavioural symptoms in Alzheimer's disease are associated with white matter lesions (WML) volume and are independent of atrophy and hypometabolism: Neuroimaging / Optimal neuroimaging measures for tracking disease progression. (7th December 2020) - Femminella, Grazia Daniela; van der Doef, Thalia; Carver, Stefan; Holmes, Clive; Ritchie, Craig W.; Lawrence, Robert M; McFarlane, Brady; Tadros, George; Ridha, Basil H; Bannister, Carol; Walker, Zuzana; Archer, Hilary; et al.
Abstract: Background: Behavioral and psychological symptoms of dementia (BPSD) are highly prevalent in Alzheimer's disease (AD) and associated with adverse outcomes. There is increasing interest in identifying the risk factors for developing BPSD among AD patients. However, the pathophysiological mechanisms underlying BPSD remain poorly understood. Here we evaluated whether BPSD are associated with WMLs volume, brain atrophy and brain metabolism in AD subjects. Method: 130 AD subjects form the Evaluating Liraglutide in Alzheimer's Disease (ELAD) trial (NCT01843075) were enrolled. The presence of BPSD was evaluated with the Neuropsychiatric Inventory Questionnaire (NPI). FLAIR and T1‐weighted imaging were performed on 3T scans. WMLs was determined on FLAIR images using the Lesion Segmentation Tool (LST) in SPM12. Hippocampal and grey matter volumes were estimated using the FreeSurfer analysis on T1 MRI. Glucose metabolism (rCMRGlc) was calculated by parametric images generated using spectral analysis with an arterial plasma input function. Result: In this AD population, NPI scores were correlated with WMLs volume (Spearman's rho=.197, p=.02), also after correcting for age. NPI scores were not correlated to hippocampal or grey matter volume and to rCMRGlc in frontal, temporal, parietal or occipital lobes. When looking at the NPI sub‐scores, WMLs volume was significantly associated with agitation/aggression (Spearman's rho=.177, p=.05) and with appetite and eating disorders (Spearman's rho=.233, p=.00). Conclusion: In this study of a clinical AD population, BPSD were associated with WMLs but not with brain atrophy and hypometabolism. This suggests that vascular changes and the prevention of vascular risk factors might play an important role in reducing the impact of BPSD in AD dementia.